1988
DOI: 10.3109/02713688808997251
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelial permeability after instillation of ophthalmic solutions containing local anaesthetics and preservatives

Abstract: The effect of the local anaesthetics oxybuprocaine (OBu) and tetracaine (Tetra) and the preservatives chlorhexidine (CH) and benzalkonium chloride (BAK) on corneal epithelial permeability was studied by fluorophotometry in normal human eyes. Five instillations of one drop ophthalmic solution of the compounds were administered to one eye at 2-minute intervals; a control solution was instilled into the fellow eye. The increase in corneal epithelial permeability, expressed as the permeability ratio between the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…Anesthetic drops are known to increase epithelial permeability. 28 This could change the thickness of the corneal stroma by osmotic pressure. However, any systematic effect probably would cancel when deriving the percent thickness change between visits as the same procedure was followed.…”
Section: Clinical Trialmentioning
confidence: 99%
“…Anesthetic drops are known to increase epithelial permeability. 28 This could change the thickness of the corneal stroma by osmotic pressure. However, any systematic effect probably would cancel when deriving the percent thickness change between visits as the same procedure was followed.…”
Section: Clinical Trialmentioning
confidence: 99%
“…Esto es debido a que la fluorofotometría es la única técnica objetiva para valorar la función barrera del epitelio corneal. La fluorofotometría ha sido empleada para el estudio de la permeabilidad del epitelio en múltiples circunstancias: autofluorescencia (17,18), en usuarios de lentes de contacto (19)(20)(21), en tratamientos tópicos con y sin conservantes (22)(23)(24)(25)(26)(27)(28)(29), después de un tratamiento quirúrgico, en pacientes con ojo seco de diversa etiología (30,31), en patologías sistémicas (32-35) y para estudios de fisiología corneal (36)(37)(38)(39)(40)(41). En un trabajo nuestro anterior observamos que el valor de permeabilidad epitelial corneal en sujetos normales es 34,4±23,5 ng/ml (27).…”
Section: Discussionunclassified
“…However, a large number of experimental and clinical studies have shown that long-term use of topical drugs may induce ocular surface changes, causing ocular discomfort, tear film instability, loss of goblet cells, inflammation, conjunctival squamous metaplasia, epithelial apoptosis, and subconjunctival fibrosis. Prolonged use of local anesthetics is associated with delay of corneal reepithelialization after wounding [69], altered lubrication and tear film [6], corneal swelling, and disruption of epithelial motility [70,71]. Lidocain, one of the most commonly used anesthetics, already when used at concentrations of 250 mg/ ml (i.e., below the clinical dosage), impairs normal wound healing [72].…”
Section: Drugs In Surgery and Follow-upmentioning
confidence: 99%